The fate of health professions education as a profession: a road less travelled - Syeda Sanaa Fatima; Rahila Yasmeen (Journal of the Pakistan Medical Association, 2023)
Objective: To explore the views of academics about the identity of Health Professions Education as a discipline, its fate and sustainability as a profession. Method: The qualitative exploratory study was conducted from February to July 2021 after approval from the ethics review committee of Islamic International Medical College, Riphah International University, Rawalpindi, Pakistan, and comprised both fulltime and part-time health professions educationists of either gender teaching in different institutions of seven cities of Pakistan; Taxila, Kamrah, Rawalpindi, Peshawar, Lahore, Multan and Karachi. Using Professional Identity theory, data was collected through semi-structured one-on-one interviews which were conducted online. The interviews were transcribed verbatim, coded and thematically analysed. Result: Of the 14 participants, 7(50%) had qualifications and experience of other specialities as well, while 7(50%) were pure health professions educationists. Overall, 5(35%) subjects were from Rawalpindi, 3(21%) were serving in multiple cities including Peshawer, 2(14%) were from Taxilla and 1(7.5%) each was from Lahore, Karachi, Kamrah and Multan. Accumulated data led to 31 codes with 3 themes and 15 sub-themes. The main themes were identity of health professions education as a discipline, its fate and sustainability. Conclusion: Health professions education has established its identity as a discipline in Pakistan, with independent, fully functioning departments in medical and dental colleges across the country. Key Words: Health professions education, Future, Health professions educationists, Profession.